Predominance of High-Level Tetracycline-Resistant Neisseria gonorrhoeae in Kenya: Implications for Global Implementation of Doxycycline Postexposure Prophylaxis for Prevention of Sexually Transmitted Infections. Issue 5 (13th May 2023) - Soge, Olusegun O.; Issema, Rodal; Bukusi, Elizabeth; Baeten, Jared M.; Mujugira, Andrew; Celum, Connie; McClelland, R. Scott; Stewart, Jenell; ,
Abstract : Most archived Neisseria gonorrhoeae samples collected from 2008 to 2012 from Kenyan women had tet (M)-encoding high-level tetracycline resistance; this could reduce the efficacy of doxycycline postexposure prophylaxis against N. gonorrhoeae . Abstract: Using archived Neisseria gonorrhoeae samples from 2008 to 2012, the prevalence of tet (M) genemediating high-level tetracycline resistance in N. gonorrhoeae was 96% among 50 Kenyan women. Determining the local and national prevalence of gonococcal tetracycline resistance and surveillance of gonococcal antimicrobial resistance can inform the implementation of doxycycline postexposure prophylaxis for STI prevention.